Regional population decline and health screening uptake in Korean adults: nationwide study using multilevel regression analysis - Jeong, Wonjeong; Kim, Woorim; Han, Kyu-Tae (Frontiers in Public Health, 2025)
BackgroundHealth screening is crucial for detecting medical needs and presenting effective alternatives. As Korea undergoes rapid demographic shifts and widening regional gaps, screening is increasingly important to identify these needs. This study explores how changes in regional population size related to health screening uptake among Korean adults.MethodsData on 182,437 adults from the 2021 Korean Community Health Survey (KCHS) were used, with health screening divided into cancer and general medical screening. Regional population size, aging index and financial independence ratio from 2012 to 2022 KOSIS were linked to our data. Generalized linear mixed effects models were applied for hierarchical logistic regression analysis of the association between the regional population size and screening, controlling for regional- and individual-level variables.ResultsDecrease in regional population size were significantly associated with lower odds ratio (OR) of receiving health screening; OR 0.85 (95% CI 0.83–0.88), as well as cancer screening; OR 0.87 (95% CI 0.85–0.90). Similar results were observed in regions with stable in population size.ConclusionOur study findings indicate the significant associations between regional population size decline and screening. Population-based policies should consider regional attributes to ensure equitable access to screening services.